Earnings differences between Chinese and Indian wage earners, 1987 - 2004 - Olivier Bargain; Sumon Kumar Bhaumik; Manisha Chakrabarty; Zhong Zhao (Institute for the Study of Labor (IZA), 2008)
This paper is one of the first comprehensive attempts to compare earnings in urban China and India over the recent period. While both economies have grown considerably, we illustrate significant cross-country differences in wage growth since the late 1980s. For this purpose, we make use of comparable datasets, estimate Mincer equations and perform Oaxaca-Blinder decompositions at the mean and quantile decompositions at different points of the wage distribution. The initial wage differential in favour of Indian workers, observed in the middle and upper part of the distribution, partly disappears over time. While the 1980s Indian premium is mainly due to higher returns to education and experience, a combination of price and endowment effects explains why Chinese wages have caught up, especially since the mid-1990s. The price effect is only partly explained by the observed convergence in returns to education; the endowment effect is driven by faster increase in education levels in China and significantly accentuates the reversal of the wage gap in favour of this country for the first half of the wage distribution.
Keywords: O15; 330; China; India; earnings; returns to education; quantile regression; Oaxaca-Blinder decomposition; Lohn; Einkommen; Bildungsertrag; Städtischer Arbeitsmarkt; Vergleich; China; Indien